THE EFFECT OF DRINKING WATER QUALITY AND PRICE ON CONSUMER SATISFACTION AT THE HIKMAH BARU REFILL DRINKING WATER DEPOT - Ririn Pandani; Yanita; Cut Sukamawati; Risna Dewi; Lisa Iryani (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
This study aims to determine the effect of drinking water quality and price on consumer satisfaction at the Hikmah Baru refill drinking water depot, Simpang Empat Village, Simpang Empat District, Asahan Regency. Where currently the refill drinking water depot has begun to develop rapidly and is very important for the lives of the surrounding community. This study uses primary data with non-probability sampling which is distributed to a sample of 100 respondents. The analysis method used is the instrument test and the classical assumption test as well as the multiple linear regression test using the help of SPSS version 29 software. The results of the test obtained Drinking Water Quality significantly influences consumer satisfaction. This is known from the sig value. which is 0.001 <0.05. Furthermore, the results of the test obtained that price significantly influences consumer satisfaction. This can be seen from the significant value of the price variable, namely sig. of 0.001> 0.05. In accordance with the results and existing theories, it can be concluded that the variables Drinking water quality and price significantly influence consumer satisfaction.